PPO.61 Variation in stillbirth rate in association with ethnicity and gestational age. (9th June 2014) - Sharma, A; Subramanya, J; Marcus, S
Abstract : Obective: To determine the variation in stillbirth rate in association with ethnicity and gestational age. Design: A retrospective audit of all stillbirths from January 2009 to February 2013. Setting: A busy District General Hospital, London, catering to a high risk, multi ethnic population. Materials and Methods: 131 cases of stillbirth (SB) were identified.103 cases were analysed after review of case notes/ database. Data was stratified according to ethnicity, completed gestational age at the time of stillbirth and the type of stillbirth. Results: There were 88 antepartum stillbirth (85%) and 15 intrapartum stillbirth (15%). Ethnicity was classified as Black, Asian, White and Mixed population. Gestational age in weeks was classified into 4 groups i.e. 24–27+6, 28 to 36+6, 37 to 40 and 40+1 onwards gestation. Majority of the stillbirths was noted in Black group (40%) followed by White group (35%), Asians (14%), Mixed group (11%). Blacks contributed to majority of antepartum stillbirths (33%) compared to White group (28%). Intrapartum stillbirths were similar in both groups (7%). Asians had only antepartum stillbirths (14%). Majority (39%) of preterm stillbirths were in White population, whilst term stillbirths in Black group (31%) outnumbered others. Conclusion: In our setting, majority of the stillbirths were in women of Black ethnicity and outcomes in Asians were better, contrary to literature. Preterm stillbirths were higher in White group, whereas term mortality was higher in Blacks as quoted in literature. This should be taken into consideration when making decisions about inducing labour in addition to similar risk variables.